2010
DOI: 10.1177/1541204010374460
|View full text |Cite
|
Sign up to set email alerts
|

Violent and Nonviolent Delinquent Behavior Among Caucasian and Hispanic Youth in Mental Health Systems-of-Care Programs

Abstract: The prevention and reduction of violent and nonviolent delinquent behavior is a public health priority. In recent years, attention has turned to ethnic disparities in delinquent behavior in efforts to target programs to youth at greatest risk. This study uses longitudinal data from a national evaluation of a federally funded children's mental health systems-of-care program to examine self-reported delinquent and violent behavior among Caucasian and Hispanic youth who entered mental health services between 1997… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 44 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…Delinquent acts, especially extreme violence, committed by juveniles attract much societal attention and often have an enormous impact. Extreme violence leads to large societal costs, directly associated with involvement of the judicial system ( Azur, Garrazza & Goldweber, 2011 ). Victimization, in addition, leads to significant costs due to the involvement of mental health services ( Delisi & Gatling, 2003 ; DeLisi et al, 2010 ; DeLisi & Piquero, 2011 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Delinquent acts, especially extreme violence, committed by juveniles attract much societal attention and often have an enormous impact. Extreme violence leads to large societal costs, directly associated with involvement of the judicial system ( Azur, Garrazza & Goldweber, 2011 ). Victimization, in addition, leads to significant costs due to the involvement of mental health services ( Delisi & Gatling, 2003 ; DeLisi et al, 2010 ; DeLisi & Piquero, 2011 ).…”
mentioning
confidence: 99%
“…MST is likely to be effective for this specific group, as it is one of the few interventions that is well adjusted to the specific characteristics of the problem behavior intended to treat, as well as to the specific risk and protective factors for the onset and continuation of the problems of extremely violent juveniles ( Farmer et al, 2002 ; Tzoumakis, Lussier, & Corrado, 2014 ). In addition, Azur and colleagues (2011) showed that although delinquency decreases over time, violence does not. Consequently, interventions are needed that reduce violence.…”
mentioning
confidence: 99%